Effectiveness Analysis of Digital Teaching Materials and Assessment for Gadget Based Application by Using Artificial Intelligence - Lenti Susanna Saragih; Jufri Darma; Sabda Dian Nurani Siahaan (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to evaluate the viability and effectiveness of the use of digitalisation of teaching materials and learning assessment of marketing management courses with artificial intelligence based on gadget applications. This study used development research with DDD-E model (decide, design, develop, evaluate). These research subjects were students from the 4th semester of the Business Education Program of Universitas Negeri Medan, with 65 students. Before being put on trial, first the product was put to test to see its validity which will be judged by three experts to measure the eligibility by looking at the material, language, and media. A practicality test was performed to see the usage practicality by looking at the Source aspect, animation aspect, visual aspect, audio aspect, evaluation aspect, and accessibility aspect. Hypothesis test performed by using paired sample T-test with experimental design before-and-after to test the effectiveness of teaching materials and study assessments as to the outcome of before-and-after treatment using teaching materials on digital-based application. The research results showed that using the digitalization of teaching materials and learning assessment of the marketing management course with artificial intelligence before and after treatment results in different learning outcomes, according to the effectiveness test. From the data, it can be seen that there is a strong and significant influence of around 64.2% between before and after the use of teaching materials and digital learning assessments of the dBUSAR application on student learning outcomes. Overall, the role of Artificial Intelligence in student learning has great potential to change the educational paradigm.